KONFLIK ARAB-ISRAEL PASCA-NAKBAH (1948-1968): KAJIAN NEW HISTORICSM PADA NOVEL 'AAIED ILA HAYFA KARYA GHASSAN KANAFANY - Bin Saiful Hafni, Izharulhak; Nasrul Latifi, Yulia; Mustari (Paramasastra : Jurnal Ilmiah Bahasa Sastra dan Pembelajarannya, 2025)
This research aims to describe the representations of history, political and social identity in the novel 'Aaeid Ila Hayfa' by Ghassan Kanafany. Using the New Historicism approach of Stephen Greenblatt's New Historicism, this analysis focuses on the interaction between literary texts and the historical-political contexts that surround it. The novel tells the story of the return of Said and Safiyya's return to Haifa after the Nakba of 1948, which is also a representation of resistance to colonialism. Representation of resistance to colonialism, identity crisis and loss of property rights experienced by the Palestinian people loss of property rights experienced by the Palestinian people. This analysis will be carried out by comparing the novel's narrative with relevant historical documents. The findings of this research shows that 'Aaeid Ila Hayfa' is not only a fictional narrative, but also as a medium to represent the collective trauma of the Palestinian people and their trauma and their struggle to maintain their national identity.